The impact of doctor-patient communication on patient satisfaction in outpatient settings: implications for medical training and practice - Xinyi Chen; Chang Liu; Pengpeng Yan; Hanle Wang; Jingjie Xu; Ke Yao (BMC Medical Education)
Abstract Poor doctor-patient communication significantly contributes to patient dissatisfaction. This study investigates the impact of doctor-patient communication quality on patient satisfaction to guide medical education, clinical training, and hospital management improvements. Using validated questionnaires, we found a significant positive correlation between overall communication quality and patient satisfaction (r = 0.539, p < 0.001). Specifically, dimensions of medical information communication (r = 0.530, p < 0.001) and communication skills (r = 0.417, p < 0.001) were significantly correlated with patient satisfaction, whereas cognitive and emotional communication dimensions were not significantly correlated. Regression analysis further demonstrated communication satisfaction as a reliable predictor of patient satisfaction (R² = 0.287, p < 0.001). We recommend enhancing healthcare providers’ communication skills and detailed medical information disclosure through targeted training programs. Emphasizing patient-centered communication strategies can substantially improve patient satisfaction and reduce doctor-patient disputes.